New techniques for cartilage magnetic resonance imaging relaxation time analysis: Texture analysis of flattened cartilage and localized intra- and inter-subject comparisons - Carballido-Gamio, Julio; Link, Thomas M.; Majumdar, Sharmila (Magnetic resonance in medicine, 2008)
MR relaxation time measurements of knee cartilage have shown potential to characterize knee osteoarthritis (OA). In this work, techniques that allow localized intra‐ and inter‐subject comparisons of cartilage relaxation times, as well as cartilage flattening for texture analysis parallel and perpendicular to the natural cartilage layers, are presented. The localized comparisons are based on the registration of bone structures and the assignment of relaxation time feature vectors to each point in the bone–cartilage interface. Cartilage flattening was accomplished with Bezier splines and warping, and texture analysis was performed with second‐order texture measures using gray‐level co‐occurrence matrices (GLCM). In a cohort of five normal subjects the performance and reproducibility of the techniques were evaluated using T1ρ maps of femoral knee cartilage. The feasibility of creating a mean cartilage relaxation time map is also presented. Successful localized intra‐ and inter‐subject T1ρ comparisons were obtained with reproducibility similar to that reported in the literature for regional T2. Improvement of the reproducibility of GLCM features was obtained by flattening the T1ρ maps. The results indicate that the presented techniques have potential in longitudinal and population studies of knee OA at different stages of the disease. Magn Reson Med 59:1472–1477, 2008. © 2008 Wiley‐Liss, Inc.